Encephaloduroarteriosynangiosis (EDAS) in young patients with cerebrovascular complications of sickle cell disease: Single-institution experience. (17th February 2017) - Winstead, Michael; Sun, Peter P.; Martin, Kenneth; Earl, Janice; Neumayr, Lynne; Hoppe, Carolyn; Vichinsky, Elliott
ABSTRACT: Moyamoya syndrome occurs in sickle cell disease (SCD) as a secondary complication of large-artery stenosis. Moyamoya increases the risk of stroke, but its optimal management in SCD is not established.  Encephaloduroarteriosynangiosis (EDAS) is a neurosurgical revascularization procedure for moyamoya whose use has been reported in SCD patients. We report the outcomes of 11 patients with SCD systematically evaluated for EDAS by a multidisciplinary team and compare the rate of stroke in patients who received EDAS to those who did not. Moyamoya syndrome was diagnosed by flow abnormalities on magnetic resonance angiography at median age of 8.2 years. Four patients deferred surgery. Seven patients underwent EDAS at median age of 19 years. There were no intraoperative complications, perioperative strokes, or deaths. Transient postoperative complications occurred in six cases (86%). On follow-up, three patients (43%) had no evidence of flow in their EDAS grafts, and one later developed a hemorrhagic stroke. Five EDAS patients (71%) had radiographically stable vasculopathy. Compared to the four patients who deferred surgery, the incidence of stroke in EDAS group was no different. The optimal use of EDAS in patients with SCD-associated moyamoya syndrome requires further investigation by a prospective, controlled clinical trial.